vp100812_elic_NominalForms_EnetseO_poss - Валентина Пуяковна Силкина (Надер); Андрей Шлуинский (Bernard Comrie, 2010)
О.Ханина собирает с В.П.Надер посессивные окончания при посессере ед. числа для звонкочередующейся основы EnetseO 'человек' O.Khanina collects with V.P.Nader possessive affixes for singular possessor in the case of a voiced alternating stem EnetseO 'person' Language_Name: Enets Language_Region: Asia Language_Country: Russia Project_Status: Complete Year: 2007 Start_Date: 2008-02-01 End_Date: 2011-01-31 Title vp100812_elic_NominalForms_EnetseO_poss